Bulk Materials Handling Handbook - Fruchtbaum, Jacob (Van Nostrand Reinhold, 1988)
The handling of bulk materials is a continuously completed projects. Much of the nomenclature has been changing science. Since very few schools teach the han brought up to date. dling of bulk materials, it is necessary for practicing en Publication of the material contained herein is not in gineers to develop their own training manuals. This book tended as a representation or warranty on the part of the is an abbreviated version of a manual used for that pur author, publisher, editors, or any other person or firm pose in our office, and developed over a period of more named herein that it is suitable for any particular use, or than 50 years. While some industrial firms follow their free from infringement of any patent or patents. own practices, the trend in the past few years has been The text is intended as a guide. When used for any to adopt the standards of equipment manufacturers' as specific project, a competent professional engineer sociations and similar organizations. The selection of should be retained to verify the assumptions, applica material and the use of drawiugs instead of photographs bility, calculations, and accuracy of the particular de is based on our experience.